Development and investigation of hybrid bio-panels based on sugarcane bagasse and coir fiber - Mawardi, Indra; Nurdin, .; Jannifar, A.; Desvita, Hera; Raaf, Auliyaa; Putra Jaya, Ramadhansyah (IIETA, 2025)
The widespread availability of bagasse and coir fiber has made them popular choices for use as composite reinforcements. Typically, composites containing bagasse or coir fiber are created using a polymer matrix. However, hybrid composites combining bagasse, coir fiber, tapioca starch, and PVAc matrices have not been identified as innovative aspects of this research. This study aims to develop and analyze a novel hybrid bio-panel by combining sugarcane bagasse (SCB) and coir fiber (CF) with a tapioca starch (TS) and polyvinyl acetate (PVAc) blend as the matrix. The bio-panels were fabricated using a hot press method with three SCB-to-CF fiber ratios (30:70, 50:50, and 70:30) and three fiber-to-matrix ratios (30:70, 40:60, and 50:50). Mechanical and physical properties, including flexural strength, density, water absorption, thermal conductivity, and fractured surface morphology, were thoroughly evaluated. Results showed that higher TS/PVAc matrix content and CF proportions improved water resistance, flexural properties, and thermal stability, though thermal conductivity decreased. Additionally, higher panel density correlated with improved flexural properties and thermal conductivity. Sample BC8, with a density of 0.737 g/cm³, achieved the lowest thermal conductivity at 0.132 W/mK. The highest flexural strength and modulus, 9.18 MPa and 485.48 MPa, were observed with a composition of 30 wt% SCB and 70 wt% CF in a TS/PVAc matrix at 70 wt%. This study concludes that SCB and CF fibers can serve as effective fillers in hybrid bio-panels, offering a sustainable material solution.